Grip strength as a mediator in the relationship between physical activity and osteoporosis in older adults: Evidence from two longitudinal cohort studies - Jinguang Gu; Bin Zhang; Xinyu Long; Xiaoqing Wang; Weikai Qin; Yongli Dong (PLoS ONE, 2026)
Background Osteoporosis is a skeletal disorder characterized by reduced bone mass and increased fracture risk. With the aging global population, its prevalence is rising, posing a significant public health challenge. Physical activity is considered an effective intervention to reduce osteoporosis risk, but the role of grip strength as a mediator remains underexplored. Methods Data from the English Longitudinal Study of Ageing (ELSA) and the Health and Retirement Study (HRS) were analyzed using generalized linear mixed models (GLMM) and mediation analysis to explore the impact of physical activity on osteoporosis and the role of grip strength. Subgroup analyses accounted for age, gender, and confounding factors. Results The prevalence of osteoporosis was 6.3% in ELSA and 14.1% in HRS. A significant negative correlation was found between physical activity and osteoporosis in both groups (ELSA: OR = 0.234, P < 0.001; HRS: OR = 0.638, P = 0.028). In those aged ≥65, physical activity had a more pronounced effect (OR = 0.478, P < 0.001). Women showed greater benefit. Mediation analysis in the ELSA group revealed that grip strength mediated 28.3% of the effect of physical activity on osteoporosis (ACME = −0.007, P < 0.001). Conclusion Physical activity, especially resistance training, reduces osteoporosis incidence by enhancing muscle strength, with grip strength playing a mediating role. These findings highlight the importance of physical activity, particularly in older women, for osteoporosis prevention.